Effect of P‐glycoprotein inhibition at the blood–brain barrier on brain distribution of (R)‐[11C]verapamil in elderly vs. young subjects - Bauer, Martin; Wulkersdorfer, Beatrix; Karch, Rudolf; Philippe, Cécile; Jäger, Walter; Stanek, Johann; Wadsak, Wolfgang; Hacker, Marcus; Zeitlinger, Markus; Langer, Oliver (British journal of clinical pharmacology, 2017)
Aims The efflux transporter P‐glycoprotein (ABCB1) acts at the blood–brain barrier (BBB) to restrict the distribution of many different drugs from blood to the brain. Previous data suggest an age‐associated decrease in the expression and function of ABCB1 at the BBB. In the present study, we investigated the influence of age on the magnitude of an ABCB1‐mediated drug–drug interaction (DDI) at the BBB. Methods We performed positron emission tomography scans using the model ABCB1 substrate (R)‐[11C]verapamil in five young [26 ± 1 years, (mean ± standard deviation)] and five elderly (68 ± 6 years) healthy male volunteers before and after intravenous administration of a low dose of the ABCB1 inhibitor tariquidar (3 mg kg−1). Results In baseline scans, the total distribution volume (VT) of (R)‐[11C]verapamil in whole‐brain grey matter was not significantly different between the elderly (VT = 0.78 ± 0.15) and young (VT = 0.79 ± 0.10) group. After partial (incomplete) ABCB1 inhibition, VT values were significantly higher (P = 0.040) in the elderly (VT = 1.08 ± 0.15) than in the young (VT = 0.80 ± 0.18) group. The percentage increase in (R)‐[11C]verapamil VT following partial ABCB1 inhibition was significantly greater (P = 0.032) in elderly (+40 ± 17%) than in young (+2 ± 17%) volunteers. Tariquidar plasma concentrations were not significantly different between the young (786 ± 178 nmol l−1) and elderly (1116 ± 347 nmol l−1) group. Conclusions Our results provide the first direct evidence of an increased risk for ABCB1‐mediated DDIs at the BBB in elderly persons, which may have important consequences for pharmacotherapy of the elderly.